AN OVERVIEW OF UPDATES ON BREAST ULTRASOUND REPORTING IN A LOW-MIDDLE-INCOME COUNTRY - Suwanto, Agnes Wanda; Nugroho, Rafiq Sulistyo; Farah Nurdiana (Department of Radiology, Medical Faculty, University of Brawijaya, 2025)
BACKGROUND AND OBJECTIVE: Ultrasound plays an essential role in the initial assessment of breast cancer. This paper review the breast ultrasound report based on ACR BI-RADS 5th edition 2013, with additional information based on a related updated journal. METHOD: A literature review was followed while conducting this study with the keywords “BI-RADS Update”, “Breast Ultrasound”, and “Update Breast Ultrasound Report”. RESULT: Minimal progress has been made since ACR BI-RADS 5th edition. Meanwhile, the clinical applicability of breast ultrasound reporting could adapt to local policies as needed. CONCLUSION: The fifth BI-RADS widely awaited version includes updates to the ultrasound. The revisions serve multiple key purposes: aligning terminology across imaging techniques such as mammography, ultrasound, and MRI; anticipating the growing use of supplementary screening methods and specialized technologies like automated breast ultrasound and elastography; and facilitating the transition toward more effective and efficient interpretation and reporting.